2010
DOI: 10.1007/s11192-010-0293-6
|View full text |Cite
|
Sign up to set email alerts
|

Citation accuracy in environmental science journals

Abstract: Citations in five leading environmental science journals were examined for accuracy. 24.41% of the 2,650 citations checked were found to contain errors. The largest category of errors was in the author field. Of the five journals Conservation Biology had the lowest percentage of citations with errors and Climatic Change had the highest. Of the citations with errors that could be checked in Web of Science, 18.18% of the errors caused a search for the cited article to fail. Citations containing electronic links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…7 Lopresti points out that even slight changes to authors' names, such as the omission of a middle initial, can impede the tracing of authors through citations to their work. 8 Many studies compare journals within a discipline. For example, Fenton studied four otolaryngology journals and found "the higher the impact factor for the journal, the lower the number of errors detected in its papers."…”
Section: Citation Accuracymentioning
confidence: 99%
“…7 Lopresti points out that even slight changes to authors' names, such as the omission of a middle initial, can impede the tracing of authors through citations to their work. 8 Many studies compare journals within a discipline. For example, Fenton studied four otolaryngology journals and found "the higher the impact factor for the journal, the lower the number of errors detected in its papers."…”
Section: Citation Accuracymentioning
confidence: 99%
“…A study of citations in social work journals found an error rate of about 41 per cent (Spivey and Wilks, 2004). Environmental science journals had an error rate of about 25 per cent (Lopresti, 2010). Citation accuracy should be critical in the medical field, but mistakes are common there as well.…”
Section: Citation Errors Ratesmentioning
confidence: 99%
“…The highest percentage of inactive URL's was found in the .com, top-level domain followed by the .gov and .org domains. Lopresti (2010) examined citations in five leading Environmental Science journals for accuracy. As many as 647 (24.41%) of the 2650 citations checked were found to contain errors.…”
Section: Decay Of Online Citationsmentioning
confidence: 99%
“…Previous studies have also showed that many URLs cited in research articles have disappeared because of several reasons (Aronsky, Madani, Carnevale, Duda, & Feyder, 2007;Carnevale & Aronsky, 2005;Goh & Ng, 2007;Lopresti, 2010;McCown et al, 2005;Sellitto, 2004). Keeping in view the disappearance nature of URL citations, this study made an attempt to investigate the availability and decay online citations cited in Science and Social Science open access journals published during 2000e2009.…”
Section: Introductionmentioning
confidence: 97%